Musings of an "Old-School" Programmer. - Jenkins, Stephen B. (Communications of the ACM, 2006)
The article presents the author's views on the traditional style of software development. The author describes the various software development applications and hardware he uses. A comparison of the tradition and modern approaches to software development is presented. The use of IDE and UML in computer software development is discussed.